Is timolol an effective treatment for pyogenic granuloma?. (12th February 2016) - Gupta, Divya; Singh, Nidhi; Thappa, Devinder Mohan
Abstract: Background: Pyogenic granuloma (PG) is a benign vascular tumor that can be treated by cautery (chemical or thermal), laser, excision, curettage, sclerotherapy, and cryotherapy. Topical timolol is emerging as a non‐invasive modality for the treatment of PGs. Methods: We recruited a series of 10 patients with PG, who received treatment with 0.5% timolol maleate ophthalmic solution applied 4 times a day, 2 drops per dose. No other medication, topical or systemic, was given. Pulse rate, blood pressure, and blood glucose were monitored at baseline and weekly thereafter for the duration of treatment. ECG was done at baseline. The efficacy of the treatment was evaluated by considering a complete response, a partial response, and no response . Results: Of 10 patients, four showed complete response within 3–24 days, with no recurrence at 3‐month follow‐up. Three patients each showed partial or no response. No local or systemic side effects were reported in any of the patients. Conclusions: The response of PGs to β blockers seems to be variable. Although topical timolol has the advantage of minimal adverse events, ease of administration, and better cosmetic outcomes, it's efficacy in PG may not be universal unlike in infantile hemangiomas. Topical timolol may be a treatment option in young children, incapacitated elderly, and over delicate areas like face, nails, and gums where invasive modalities are not desirable.